Cross-linked actin networks (CLANs) are present in lamina cribrosa cells. Issue 10 (7th August 2010) - Job, Raly; Raja, Vignesh; Grierson, Ian; Currie, Laura; O'Reilly, Steven; Pollock, Natalie; Knight, Emma; Clark, Abbot F
Abstract : Aims: A study was undertaken to determine and compare the F-actin staining patterns in the cells of the lamina cribrosa (LC) of normal, dexamethasone (DEX)-treated and glaucomatous dissected tissue and cell cultures. Methods: About 30 dissected donor eyes and nine cell lines provided the human specimens; 25 eyes and 20 primary cell cultures provided the bovine material. Appropriate samples were exposed to 1×10 −7 M DEX for up to 14 days. LC tissue and cells were stained with Phalloidin-Alexa 488 to identify F-actin, and all samples were examined by confocal or epifluorescent microscopy. Results: Both in the LC tissue and LC cell cultures the dominant actin arrangement was bundles of stress fibres. However, cross-linked actin networks (CLANs) were identified in the tissue and in culture. These were markedly increased by steroid treatment and were particularly large and abundant in cultures from glaucoma donors. CLANs were not associated with optic nerve head astrocytes. Conclusions: The presence of abundant stress fibres in situ and in vitro highlights the biomechanical contribution of LC cells. However, the identification of CLANs in these cells shows that they are not exclusive to the trabecular meshwork, the only other place they have been found, and may have a role in glaucoma pathology.